Circular Gold Nanodisks with Synthetically Tunable Diameters and Thicknesses. (15th January 2018) - Cui, Ximin; Qin, Feng; Ruan, Qifeng; Zhuo, Xiaolu; Wang, Jianfang
Abstract: 2D or pseudo‐2D plasmonic Au nanocrystals, such as circular Au nanodisks, possess unique plasmonic properties. Circular Au nanodisks not only possess two large surfaces with circular symmetry but also exhibit the wide tunability for their plasmon resonance. However, the lack of effective synthetic methods for producing size‐tunable and monodispersed circular Au nanodisks hinders further studies on their properties and applications. Herein, the synthesis of uniformly sized circular Au nanodisks with synthetically tunable diameters and thicknesses is reported. By performing mild anisotropic oxidation on pregrown Au nanoplates with different thicknesses, the thicknesses of the obtained nanodisks are varied from ≈10 nm to ≈50 nm. The nanodisk diameters are tailored from ≈50 nm to ≈150 nm by controlling the oxidation time. Moreover, both homodimers and heterodimers made of circular Au nanodisks are constructed using molecular linkers. They exhibit rich plasmon modes. In particular, dark multipolar plasmon resonance modes can be excited and observed in the asymmetric heterodimers. Such circular Au nanodisks with controllable sizes, large atomically flat surfaces, and a dominant dipolar plasmon mode are ideal building blocks for constructing plasmonic assemblies and plasmon‐coupled systems with desired plasmonic properties and functions. Abstract : Colloidal circular Au nanodisks with controllable diameters and thicknesses are synthesized. Their in‐plane dipolar plasmon resonance can be synthetically varied from the visible to near‐infrared region. Homodimers and heterodimers in different geometrical configurations are assembled out of the circular Au nanodisks with different thicknesses. They display rich plasmon modes that can rarely be seen on other dimeric metal nanostructures.